Does higher education enhance public perception of the environment: a quasi-natural experiment based on higher education expansion - Xie, Hanjin; Wu, Fengquan; Li, Jun (Frontiers in Psychology, 2025)
It is now well acknowledged that environmental challenges threaten public health. As knowledge proliferates, public awareness of environmental issues escalates, along with heightened sensitivity to these concerns. This study seeks to utilize the 1999 ‘college entrance examination enlargement’ policy as a quasi-natural experiment. Utilizing data from the 2020 China Family Panel Studies (CFPS), a perception score was established on a scale of 0–10, and a cohort difference-in-differences model was employed to assess the influence of higher education on public environmental perception. The research indicated that advanced education has enhanced the public’s environmental awareness levels. Mechanism studies indicate that higher education enhances environmental awareness by augmenting individuals’ scientific literacy through extended years of study, cultivating favorable views toward the internet, and refining internet usage skills. The enhancement of rational thinking skills via higher education constitutes another avenue of influence. The influence of higher education on improving public environmental awareness demonstrates considerable variability across several aspects. The research demonstrates that voluntary and market-incentive-based environmental restrictions have distinct moderating functions in this process. This research clarifies the fundamental mechanisms of enhanced environmental perception among Chinese inhabitants, offering additional insights into the evolution of environmental consciousness and behavior among the Chinese populace. Moreover, it provides significant insights for policy enhancement, educational philosophy, and urban–rural integration.